Paracoccidioides brasiliensis: utilização de animais como sentinelas para presença do fungo no Rio Grande do Sul, Brasil - Albano, Ana Paula Neuschrank (2012)
The paracoccidioidomycosis (PCM) is one of the most important systemic mycoses in Latin America, especially in Brazil. Although the Rio Grande do Sul is considered endemic area of the disease, there are few studies on the ecology of Paracoccidioides brasiliensis in the state. In this sense, the study aimed to detect infection by P. brasiliensis in animals using them as sentinels for detection of the agent in the region. Serology was performed by the techniques of double radial immunodiffusion in agar gel (AGID) and ELISA for detection of anti-gp43 of P. brasiliensis in wild animals served by Núcleo de Reabilitação da Fauna Silvestre UFPel, and horses from different stables in the region of Bagé. Serology was performed in 128 wild animals, and about 20% of these were positive on ELISA. The presence of anti-gp43 was detected in animals from the mesoregion of Southeast Riograndense and Metropolitan of Porto Alegre. There was no significant difference in seropositivity with respect to gender, age, order and habits of animals (p> 0.05), however seropositivity differed between the conjugates used (p <0.001). The study regarding horses included 200 animals from different places, which 12% had antigp43 antibodies in ELISA, with rates ranging from 0 to 30% according to the place of origin (p <0.001). Neither the wild animals nor equines were positive by immunodiffusion. The results indicate the presence of the fungus P. brasiliensis in different mesoregions of Rio Grande do Sul.